2017
DOI: 10.1016/j.celrep.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA-Seq Reveals Hypothalamic Cell Diversity

Abstract: SUMMARY The hypothalamus is one of the most complex brain structures involved in homeostatic regulation. Defining cell composition and identifying cell-type-specific transcriptional features of the hypothalamus is essential for understanding its functions and related disorders. Here, we report single-cell RNA sequencing results of adult mouse hypothalamus, which defines 11 non-neuronal and 34 neuronal cell clusters with distinct transcriptional signatures. Analyses of cell-type-specific transcriptomes reveal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

54
513
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 509 publications
(599 citation statements)
references
References 47 publications
54
513
2
Order By: Relevance
“…The paraventricular oxytocin receptor is also involved in social buffering actions. 89 On the other hand, it has been reported that there is no mRNA expression of the oxytocin receptor in parvocellular hypothalamic CRH-positive neurones of rats 90,91 and in hypothalamic CRH neurones of mice, 92 and oxytocin has been shown to reduce the frequency of the spontaneous excitatory postsynaptic current in some CRH neurones of mice. 61 Activation of GABAergic neurones has been shown to be involved in the inhibitory actions of oxytocin on anxiety-related behaviour and the hypothalamic-pituitary-adrenal axis.…”
Section: Hypothalamic Paraventricular Nucleusmentioning
confidence: 99%
“…The paraventricular oxytocin receptor is also involved in social buffering actions. 89 On the other hand, it has been reported that there is no mRNA expression of the oxytocin receptor in parvocellular hypothalamic CRH-positive neurones of rats 90,91 and in hypothalamic CRH neurones of mice, 92 and oxytocin has been shown to reduce the frequency of the spontaneous excitatory postsynaptic current in some CRH neurones of mice. 61 Activation of GABAergic neurones has been shown to be involved in the inhibitory actions of oxytocin on anxiety-related behaviour and the hypothalamic-pituitary-adrenal axis.…”
Section: Hypothalamic Paraventricular Nucleusmentioning
confidence: 99%
“…However, there are different types of tanycytes and whether these different tanycyte subtypes can be characterized using a molecular signature is necessary. Using the scRNA-seq data, Chen et al have identified Slc17a8 and Col25a1 as potential markers for α1 and β tanycyte subtypes, respectively [17]. Clustering analysis has identified Rax as tanycyte cell cluster marker, indicating that tanycytes are transcriptionally distinct from ependymocytes and other cell types [17].…”
Section: Tanycyte Genetic Markersmentioning
confidence: 99%
“…Using the scRNA-seq data, Chen et al have identified Slc17a8 and Col25a1 as potential markers for α1 and β tanycyte subtypes, respectively [17]. Clustering analysis has identified Rax as tanycyte cell cluster marker, indicating that tanycytes are transcriptionally distinct from ependymocytes and other cell types [17]. Notably, although specific marker genes (or combinations of marker genes) are used to roughly separate tanycyte subtypes, many genes exhibit a gradient, rather than a clear-cut distribution across tanycyte subpopulations which are consistent with the notion that tanycytes may be composed of continuous cell trajectory with transition zones between different subtypes.…”
Section: Tanycyte Genetic Markersmentioning
confidence: 99%
“…Eberwine et al (1992) [98] performed gene expression analysis on individual, freshly dissociated hippocampal neurons. More recently, single-cell isolation has now been conducted using laser-capture microdissection (LCM) methods; e.g., [37, 47, 56, 239, 456], or cell sorting methods (e.g., [64, 69, 95; 160; 264; 278; 368]; also see [312, 351]). Thus, single cell isolation methods first used for the purposes of morphological and structural investigation evolved for use in biochemical, molecular and functional analyses.…”
Section: Historical Antecedentsmentioning
confidence: 99%
“…Using Drop-Seq, a method that allows for single-cell transcriptomics to be performed in a manner that preserves the cell provenance of the RNA that is extracted [264], Chen et al (2017) [64] reported single-cell RNA sequencing results from the adult mouse hypothalamus. They used clustering analysis to identify 11 non-neuronal (including oligodendrocytes, astrocytes, ependymocytes, tanycytes, microglia, and macrophages) and 34 neuronal cell types (including 15 glutamatergic and 18 GABAergic clusters, and one histaminergic neuron cluster) from tissue dissociated from manually dissected hypothalamus, and confirmed some of their key findings by performing immunohistochemistry for neuropeptides or comparing their results with those found in the publicly available Allen Brain Atlas.…”
Section: Molecular Mining Of the Hypothalamusmentioning
confidence: 99%